Pelatihan Digital Marketing dan Branding Olahan Pangan di Desa Hegarmukti sebagai Upaya Meningkatkan Daya Jual UMKM - Wicaksana, Primaraga Sumantri Indra; Permana, Indra; Rismawati; Setyawan, Wisnu; Suriyanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
The training, which aims to increase the knowledge of UMKM on the use of Digital Marketing and Social Media Marketing, will be carried out directly by holding seminars and workshops. This training will later be given by 5 speakers with participants from UMKM actors who produce ready-to-sell processed products in Hegarmukti Village, Cikarang Pusat District, Bekasi. The training began with holding a seminar to provide an understanding of Digital Marketing and Social Media Marketing. Implementation of Digital Marketing and Social Media Marketing training activities as PKM activities with the aim of increasing knowledge of Digital Marketing and Social Media Marketing to UMKM actors in Hegarmukti Village, Cikarang Pusat District, Bekasi